Psychosomatic correlations and mental disorders in diabetes mellitus - Yurtsenyuk, Ольга; Napreenko, Олександр; Napreenko, Наталія (Psychosomatic Medicine and General Practice, 2021)
Mental disorders in diabetes mellitus, depending on the contingent of examined patients occur in 1.3-100% of cases. The prevalence of these disorders among the elderly reaches almost 100%. The aim of this study was to study the structure of mental disorders in diabetes. 42 patients with type II diabetes mellitus aged 40 to 78 years were examined (mean age 59.5 years). All patients had mental disorders of varying severity. A combination of instenon, actovegin and glycised was used to treat neurosis-like disorders and dementia in patients with diabetes. The average duration of the combined course of treatment was 4 weeks. The main research methods were clinical-psychopathological, clinical-anamnestic, experimental-psychological.